Proceedings of the Forty-Sixth Annual ACM Symposium on Theory of Computing 2014
DOI: 10.1145/2591796.2591838
|View full text |Cite
|
Sign up to set email alerts
|

Communication lower bounds via critical block sensitivity

Abstract: Abstract. We use critical block sensitivity, a new complexity measure introduced by Huynh and Nordström (STOC 2012), to study the communication complexity of search problems. To begin, we give a simple new proof of the following central result of Huynh and Nordström: if S is a search problem with critical block sensitivity b, then every randomised two-party protocol solving a certain two-party lift of S requires Ω(b) bits of communication. Besides simplicity, our proof has the advantage of generalising to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 67 publications
0
39
0
Order By: Relevance
“…We also define MBS (and all other complexity measures introduced later in this section) with respect to real-valued functions over {0, 1} 𝑛 . This differs from block sensitivity, which is usually (though not always [13]) studied in the context of boolean-valued functions. The generalization to real-valued 𝑓 will be immaterial to some of our proofs, permitting us to draw more general conclusions regarding the monomial structure of multilinear polynomials; see Section 5 for more details.…”
Section: Monotone Block Sensitivitymentioning
confidence: 99%
“…We also define MBS (and all other complexity measures introduced later in this section) with respect to real-valued functions over {0, 1} 𝑛 . This differs from block sensitivity, which is usually (though not always [13]) studied in the context of boolean-valued functions. The generalization to real-valued 𝑓 will be immaterial to some of our proofs, permitting us to draw more general conclusions regarding the monomial structure of multilinear polynomials; see Section 5 for more details.…”
Section: Monotone Block Sensitivitymentioning
confidence: 99%
“…We lift the query results of Section 4 to a communication model using the result of [HN12,GP18], Theorem 1. The high-level idea is to use the replication technique (Section 4.1).…”
Section: N-player Hardnessmentioning
confidence: 99%
“…v∈V P [HN12]. and[GP18] have proved that this lifting of the problem to communication is as hard as the query problem, even for randomized communication model.Theorem 1 ([HN12, GP18]). CC(EndOfLine(Pyr(T )) = Θ(QC(EndOfLine(Pyr(T ))) = Θ( √ T ).…”
mentioning
confidence: 99%
“…In [Göös and Pitassi, 2014] it is shown that there exists a constant degree graph D with N vertices where both the randomized communication complexity of the problem is Θ( √ N ). The proof is done in three steps.…”
Section: Proof Of Theorem 21mentioning
confidence: 99%